Core and peripheral organisations in prevention: Insights from social network analysis. (23rd July 2020) - Held, Fabian; Hawe, Penelope; Roberts, Nick; Conte, Kathleen; Riley, Therese
Abstract: Issue: Formal (eg funded) community‐level organisational collaborations are becoming more common in prevention. Rapid methods to assess organisational relationships could allow us to consider the significance of any pre‐existing relationship patterns in communities that might impact on collaboration effectiveness. Insights may identify new options for practice. Methods: We used social network analysis to study organisations engaged in prevention but not (yet) part of a formal purposive collaboration. Within a single community, we identified organisations providing programs in chronic disease prevention. We used whole network analysis methods to describe the extent to which organisations were aware, had contact, coordinated activity and/or collaborated more intensively. We also identified the contribution made to prevention locally. Results were compared with key informant interviews. Results: There was an identifiable network structure, with more relationships across the network than one would expect by chance. The network had a core‐periphery structure, meaning that, in terms of the relationships we measured, there were highly connected organisations who were strongly interlinked with each other (the core), alongside less connected organisations that were linked to the core but not to each other (the periphery). Core organisations were significantly more likely to have expertise in prevention and to have prevention staff. Conclusions: To our knowledge, it is new to identify inherent or "pre‐existing" core‐periphery structures in interorganisational health promotion. Yet, core‐periphery structures are common in many social settings. They advantage entities in the core and are prone to further entrenchment. So what?: Our results map and quantify intuitive understandings about organisational "key players", thus enabling practitioners/organisations to critically reflect on what their role should be when it comes to activating communities ie to embed, or attempt to counterbalance, pre‐existing power structures.